2000
DOI: 10.1001/archotol.126.12.1478
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computed Tomography in Determining the Presence or Absence of Metastatic Retropharyngeal Adenopathy

Abstract: The presence of retropharyngeal node metastasis cannot be determined by computed tomographic imaging alone. Arch Otolaryngol Head Neck Surg. 2000;126:1478-1481

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 7 publications
2
24
0
Order By: Relevance
“…One study of patients with advancedstage head and neck squamous cell carcinoma found that CT had a sensitivity and specificity 50% and 70%, respectively, for the evaluation of positive retropharyngeal nodes. 12 In the case of the patient in this report, MRI was an effective method of determining the presence of the enlarged retropharyngeal node.…”
Section: Discussionmentioning
confidence: 71%
“…One study of patients with advancedstage head and neck squamous cell carcinoma found that CT had a sensitivity and specificity 50% and 70%, respectively, for the evaluation of positive retropharyngeal nodes. 12 In the case of the patient in this report, MRI was an effective method of determining the presence of the enlarged retropharyngeal node.…”
Section: Discussionmentioning
confidence: 71%
“…It occurs most commonly in tumors of the tonsil and lateral pharyngeal wall and seldom in tumors of the base of tongue . Few studies of the diagnostic accuracy of the various imaging modalities for the detection of RPLN metastasis have been conducted in which pathologic confirmation was available . Morrissey et al demonstrated 50% sensitivity and 70% specificity of CT to correctly identify metastasis in patients when compared to RPLND specimens.…”
Section: Discussionmentioning
confidence: 99%
“…13,20 In view of the accuracy of preoperative imaging observed in this study, the findings of earlier reports may reflect older technology with poor resolution images. However, several earlier reports corroborating preoperative imaging with pathologic results suggested the clinical utility of CT scanning in this context is poor.…”
Section: Predictors Of Rpln Statusmentioning
confidence: 59%